Differential effect on survival of pelvic lymph node dissection at radical cystectomy for muscle invasive bladder cancer. Issue 3 (March 2015) - Larcher, A.; Sun, M.; Schiffmann, J.; Tian, Z.; Shariat, S.F.; McCormack, M.; Saad, F.; Fossati, N.; Abdollah, F.; Briganti, A.; Buffi, N.; Graefen, M.; et al.
Abstract Purpose To compare long-term cancer outcomes after radical cystectomy (RC) alone or RC with pelvic lymph node dissection (PLND) according to different age and comorbidities categories. Methods Using the SEER-Medicare dataset, 3314 patients diagnosed with urothelial carcinoma of the urinary bladder and treated with RC alone or RC with PLND were identified. After propensity score matching to reduce potential selection bias, all cause mortality (ACM)-free and cancer specific mortality (CSM)-free survival rates were estimated. Multivariable regression models (MVA) addressed the effect of PLND on ACM and CSM. Subgroups analyses according to age and comorbidities were performed. Results After matching, 688 and 688 patients treated with RC alone or RC with PLND remained. The 5-year ACM-free survival rate was 36 after RC alone and 45% after RC with PLND (p < 0001). In MVA, PLND exerted a protective effect on ACM (HR 0.77, p < 0.001). The 5-year CSM-free survival rate was 54 after RC alone and 65% after RC with PLND (p < 0.001). In MVA, PLND exerted a protective effect on CSM (HR 0.71, p < 0.001). Similar results were observed in younger (age ≤75) and healthier (CCI = 0) patients, where PLND exerted a protective effect on ACM (HR 0.64, p = 0.001) and CSM (HR 0.65, p = 0.01). Conversely, in older (age >75) and sicker (CCI ≥1) patients, PLND was not associated with ACM (HR 0.98, p = 0.8) or CSM (HR 1.01, p = 0.9). Conclusions RC with PLND is associated with improved all cause and cancer specific survival in younger and healthier RC candidates but not in older and sicker patients.